Corrosion Behavior of Al6061-T6 by GTAW with Different Filler Metals - Suherman, Suherman; Muharnif; Lubis, Riadini Wanty; Irfansyah; F.X.A , Wahyudianto (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
This study aims to compare the effect of filler metal of gas tungsten arc welding (GTAW) on the corrosion rate of Al6061 alloy weld metals. Three different filler metals, ER4043, ER4047, and ER5356, were used in the GTAW welding process. The corrosion rate characteristics of butt weld joints were studied using potentiodynamic testing in a 3.5% NaCl solution. The microstructure of the corroded weld metal was analyzed using Scanning Electron Microscopy (SEM). Results showed that filler metals affect the corrosion resistance of weld metal. It was found that ER4043 and ER4047 are more susceptible to corrosion, while ER5356 shows good corrosion resistance compared to the other filler metals. SEM observations revealed that dominant pitting corrosion was found in all welded joints and the base metal, with pit diameters ranging from 10 to 60 μm. Moreover, it was found that the Heat-Affected Zone was more susceptible to corrosion compared to the weld metal zone. Finally, welding of Al6061 using ER5356 filler metal is more recommended due to its superior resistance to pitting corrosion compared to the other types of joints.